Design, Preparation, and Characterization of Novel Calix[4]arene Bioactive Carrier for Antitumor Drug Delivery - An, Lin; Wang, Jia-wei; Liu, Jia-dong; Zhao, Zi-ming; Song, Yuan-jian (Frontiers in Chemistry, 2019)
An amphiphilic and bioactive calix[4]arene derivative 8 (CA) is designed and successfully synthesized from tert-butyl calix[4] arene 1 by sequential inverse F-C alkylation, nitration, O-alkylation, esterification, aminolysis, reduction and acylation reaction. The blank micelles of FA-CA and doxorubicin (DOX) loaded micelles FA-CA-DOX are prepared subsequently undergoing self-assembly and dialysis of CA and DSPE-PEG2000-FA. The drug release kinetics curve of the encapsulated-DOX micelle demonstrates a rapid release under mild conditions, indicating the good pH-responsive ability. Furthermore, the cytotoxicity of DOX-loaded micelle respect to the blank micelle against seven different human carcinoma (A549, HeLa, HepG2, HCT116, MCF-7, MDA-MB231, and SW480) cells has been also investigated. The results confirm the more significant inhibitory effect of DOX-loaded micelle than those of DOX and the blank micelles. The CDI calculations show a synergistic effect between blank micelles and DOX in inducing tumor cell death. In conclusion, FA-CA micelles reported in this work was a promising drug delivery vehicle for tumor targeting therapy.